Validation of normal and frictional contact models of spherical bodies by FEM analysis - H Khawaja; K Parvez (International Journal of Multiphysics, 2016)
Contact forces between two spheres are computed, including the contact pressure (normal) and the frictional stress (tangential) using a finite element method (FEM). A CAD model of a part of a sphere was developed. A mesh was created using ANSYS® Solid 186, 20-Noded hexahedral element and analyzed for its sensitivity. ANSYS® Contact 174 and Target 170, 8-Noded surface elements were used. Contact pressure and frictional stress contours were calculated by varying the displacements. Normal and Tangential contact forces were computed by integrating contact pressure and frictional stress over the contact surface. The values obtained for the normal force were compared with the non-linear spring model as given by Hertz [1]. Similarly values of the tangential force were compared with the model of Mindlin and Deresiewicz (MD) [2]. The FEM results were found to be in agreement with the models.